Academic Outcomes of Children with Isolated Orofacial Clefts Compared with Children without a Major Birth Defect. (May 2015) - Knight, Jessica; Cassell, Cynthia H.; Meyer, Robert E.; Strauss, Ronald P.
Objective: To compare academic outcomes between children with orofacial cleft (OFC) and children without major birth defects. Design and Setting: In 2007–2008, we mailed questionnaires to a random sample of mothers of school-aged children with OFC and mothers of children without major birth defects (comparison group). The questionnaire included Likert-scale, closed-ended, and open-ended questions from validated instruments. We conducted bivariate and multivariable analyses on parent-reported educational outcomes and bivariate analyses on parent-reported presence of related medical conditions between children with isolated OFC and unaffected children. Patients/Participants: A random sample of 504 parents of children with OFCs born 1996–2002 (age 5–12 years) were identified by the North Carolina Birth Defects Monitoring Program. A random sample of 504 parents of children without birth defects born 1996–2002 was selected from North Carolina birth certificates. Of the 289 (28.7%) respondents, we analyzed 112 children with isolated OFC and 138 unaffected children. Main Outcome Measures: Letter grades, school days missed, and grade retention. Results: Parents of children with isolated OFC reported more developmental disabilities and hearing and speech problems among their children than comparison parents. Children with isolated OFC were more likely to receive lower grades and miss more school days than unaffected children. Because of the low response rate, results should be interpreted cautiously. Conclusion: Children with isolated OFC may have poorer academic outcomes during elementary school than their unaffected peers. Future studies are needed to confirm these results and determine whether these differences persist in later grades.